Validation of tilling populations in diploid and hexaploid wheat - Rothe, Nolan (Kansas State University, 2010)
TILLING (Targeting Induced Local Lesions IN Genomes) is a high-throughput, reverse genetics strategy for scanning mutagenized populations for point mutations in loci of interest. Originally, TILLING was used to investigate gene function in Arabidopsis and has since been similarly applied for gene functional analysis in other organisms. TILLING also allows the generation of novel genetic variation in specific genotypes and, thus, has been implemented as a tool for crop improvement. Ethyl methanesulfonate (EMS) is a widely used mutagen to induce point mutations in most TILLING protocols. M1 plants are then self-pollinated and M2 seed harvested. A single seed is grown from each M2 progeny and tissue taken for DNA isolation. M3 seed is cataloged. DNA is pooled to increase the efficiency and aid in mutation detection. Polymerase chain reaction (PCR) is used to amplify a locus of interest using the M2 DNA pools as a template. The PCR products are digested with an endonuclease that cleaves mismatched, mutant DNA, and the digested products are visualized. The pools for which PCR products are positive for a mutation are deconvoluted to determine which individual plant of the pool was responsible for the mutation. DNA from the positive individual is sequenced to determine the type of mutation (missense, nonsense, synonymous). Individuals with mutations that are more likely to disrupt gene function (nonsense and certain missense) are studied further by growing the corresponding M3 generation. In bread wheat, Triticum aestivum, TILLING is complicated by polyploidy: genes that have homoeologs require that the functionality of each be studied. If functional homoeologs are present for all three genomes, mutants must be identified for each homoeolog, followed by successive intercrossing to produce a triple mutant plant. As a model for wheat genetics, we propose TILLING in diploid wheat. EMS mutant populations were created in diploid wheat (Triticum monococcum ssp. monococcum) and the hexaploid bread wheat cultivar ‘Jagger’. The diploid and hexaploid wheat populations were screened for mutations at the waxy locus, GBSS1, as a validation of our population and for comparative analysis of mutation rates in 2x and 6x wheat. For diploid wheat, GBSSI was screened in 716 M2 plants, and one mutant was found for 1.9 Mb screened. 3 For hexaploid wheat, GBSSI was screened in 518 M2 plants, and 30 mutants were identified within a total of 657 Kb screened, giving a mutation frequency of one mutation per 22 Kb. The reasons for this vast difference in mutation frequency between diploid and hexaploid wheat are discussed. The diploid wheat population was further examined by screening for mutations within four lignin biosynthesis candidate genes, for a total of 2 Mb screened. A single mutant was discovered for both of the lignin genes PAL6 and HCT, giving a mutation frequency of one mutation per 1 Mb screened.
Keywords: TILLING; Triticum monococcum; EMS mutagenesis; wheat; diploid; Triticum aestivum; Agriculture, Plant Culture (0479); Biology, Genetics (0369); Biology, Molecular (0307)